A Retrospective Study of Adherence to Malaria Treatment Guidelines for Children in Rural Health Facilities of Southwest Nigeria - Saka SA; Fakeye OT (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Background: The World Health Organisation (WHO), in 2006 and in 2010, published malaria treatment guidelines for effective case management of malaria. This study was carried out to assess the adherence of prescribers to these guidelines. Method: A retrospective pre-intervention study of adherence to malaria treatment guidelines in selected hospitals of Oyo State was carried out. Convenience sampling was used to select the case records of children below five years of age who were treated for uncomplicated malaria at the out- patient departments of selected hospitals between January and June 2010. Specifically, the use of Artemisinin-Combination Therapy (ACT) and diagnostic procedures for malaria were evaluated. Result: The records of 1445 children were studied. Chloroquine mono therapy was the most frequently used antimalarial treatment (380; 26.3%). ACTs were prescribed in 35.1% cases, artesunate mono therapy for 3.6% and non-recommended antimalarial combinations for 26.1% of cases. Parasitological diagnosis of malaria was carried out in 17.2% children. Thirty six children (2.5%) with negative microscopic results received anti-malarial drugs. Lack of clinical improvement was observed among 0.8% of the children who were prescribed various ACTs. Conclusion: The study identified non-adherence to WHO malaria treatment guidelines. The prescribers relied more on clinical judgement than parasitological diagnosis of malaria. Adequate and continuous training of health workers on case management of malaria is recommended.